Product Development Strategy Based on Customer for Mobile Application Development (Case Study: Pleasurr) - Mochammad Fajar, Febriyan; Rahardjo, Budi (The Indonesian Journal of Business Administration, 2016)
Abstract.Pleaurra is a startup which focusing on using technology to solve the problems. In this case, the problem to be solved by Pleaurra is leisure, where people of large cities get bored routines.  Large Cities which is crowded and busy, making populated filled with daily routines are boring. Most people just take advantage of the long holiday time to release their fatigue. As a result of a long holiday full of people  those who want a vacation, because of that impacted in  overcrowding in some tourism areas. The mission of Pleaurra is helping people  to discover and find a unique experience that was around of them by providing mobile application marketplace for unique experiences. A unique experience is activities outside the daily activities that give effect to release stress. In that case, everyone has different interests activities to to relieve their stress, that is a challenge for Pleaurra to build a mobile application based on customer development. This paper’s purpose is to explain and explore the suitable product development strategy by performing benchmarking to the other startups, and literature reviews of product development methodologies.  Keywords: Mobile Applications, Unique Experiences, Product Development, Customer Development